Mobile phone use and its effect on quality of sleep in medical undergraduate students at a tertiary care hospital - Arnav Kadian; Rakesh Mittal; Mahesh Chander Gupta (Open Journal of Psychiatry and Allied Sciences, 2019)
Background: Professional college students are very prone to sleep deprivation and have poor quality of sleep. Mobile phone use may have a significant impact on sleep quality and length. There is paucity of information regarding mobile phone usage and quality of sleep among the medical students in India. The present study was undertaken to evaluate the prevalence of mobile phone use among medical undergraduate students and its effect on sleep quality and daytime sleepiness. Methods: This was a cross-sectional study involving 100 medical undergraduate students. Participants were categorised into low, medium, and high mobile phone users based on duration of mobile phone use and frequency of calls/ short message service (SMS) per day. Sleep quality and daytime sleepiness were assessed by the Pittsburgh Sleep Quality Index (PSQI) and the Epworth sleepiness scale (ESS) questionnaires respectively. The impact of phone usage on various sleep quality parameters was also assessed. Results: A total of 36%, 32%, and 32% students were in high, medium, and low mobile phone users groups respectively. The mean PSQI scores were 4.57±1.22, 5.56±1.01, and 7.44±1.21 (p<0.0001) for the low, medium, and high users respectively while the corresponding values for mean ESS scores were 6.23±1.55, 7.16±2.06, and 9.26±1.76 (p<0.0001; one way ANOVA=23.93). All the sleep quality parameters except habitual sleep efficiency and use of sleep medications were adversely affected with increasing mobile phone usage. Conclusion: Increasing mobile phone use adversely affects the sleep quality and causes daytime sleepiness among the medical undergraduate students.